Effects of Pr proportion on the resistivity, structure, grain size and Mn valence of the Ca1-xPrxMnO3 powders. (December 2016) - Zhang, Jiajing; Qi, Liying; Li, Yunjiao; Li, Jialong; Fu, Qiuyue; Meng, Xianwei; Hao, Sue
Graphical abstract: Highlights: Improved electrical conductive properties of Ca1-x Prx MnO3 (0 ≤ x ≤ 0.3) powders. Interactions among Mn valence, structure and resistivity of Ca1-x Prx MnO3 powders. Ca0.75 Pr0.25 MnO3 powders as a superior candidate for electronic application. Abstract: The Ca1-x Prx MnO3 (0 ≤ x ≤ 0.3) powders were synthesized by sol-gel auto-combustion technology and the inherent relations among chemical composition, structure, and electrical properties of the Ca1-x Prx MnO3 powders were elucidated. The results indicate that the resistivity decreases first and then increases with the increase in x and its lowest value is 0.3503 Ωm with x = 0.25. X-ray diffraction results indicate that with the increase in x, the diffraction intensity of (220) crystal plane is strengthened and the diffraction peaks move to small angles. Through SEM images, it can be found that powders have the minimum grain size and the distribution of grain size is uniform at x = 0.25. With the increase in Pr proportion, the distortion of unit cell is intensified and the resistivity changes correspondingly. The resistivity of the Ca1-x Prx MnO3 powders is inversely proportional to the ratio of Mn 3+ /Mn 4+, the resistivity becomes lower when the ratio of Mn 3+ /Mn 4+ gets larger.